Performing Ruins - Murray, Simon; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Palgrave Macmillan, 2020)
This book engages with the relationship between ruins, dilapidation, and abandonment and cultural events performed within such spaces. Following the author$1 (Bs fieldwork in the UK, Bosnia Herzegovina, Poland, Germany, Greece, and Sicily, chapters describe, investigate, and reflect upon live performance events which have taken place in sites of decay and abandonment. The book$1 (Bs main focus is upon modern economic ruins and ruins of warfare. Each chapter provides several case studies based upon the author$1 (Bs own site visits and interviews with actors, directors, producers, curators, writers, and other artists. The book contextualises these events within the wider framework of Ruin Studies and provides brief summaries of how we might understand the ruin in terms of time, politics, culture, and atmospheres. The book is particularly preoccupied with artists$1 (Breasons and motivations for placing performance events in ruined spaces and how these work dramaturgically.s
1. Introduction: Ruining the Project, Subjectivities, Fields and Methods -- 2. Ruins in Context - Context in Ruins -- 3. Performing the Antiquary: Classical Ruins in the Greek Imaginary -- 4. Nature$1 (Bs Ruins -- 5. Dissonance and Contestation: Ruining Heritage and its Alternatives -- 6. Legacies of War: Performing Balkan Ruins -- 7. Ruins of Capital -- 8. After Communism and the Cold War: a Ruined Inheritance -- 9. Conclusion: Ruining the Ruin or Pausing at a Partial View -- .s
Keywords: Performing arts; Theater; Actors; Performing Arts; Contemporary Theatre; Performers and Practitioners; Applied Theatre